SISTEM PENDUKUNG KEPUTUSAN PERENCANAAN AKADEMIK DENGAN METODE BEST FIRST SEARCH ( Studi Kasus di Sekolah Tinggi Teknologi Adisutjipto ) - Atika Rina; Anton Setiawan Honggowibowo; NurCahyani Dewi Retnowati (Compiler, 2012)
With the rapid growth in current technology, academic systems in higher education has been computerized. Academic who has a computerized system is considered more effective. The computerized system has can be used to plan the academic activities of students for taking Strata 1 at the College of Technology Adisutjipto. The system uses Decision Support System (DSS) to give some conditions on Best First Search (BFS) method so that the method can be used in a subsequent advisory list of the best courses in accordance with the terms that have been obtained, which will help students in making academic decisions. Of the BFS method, students are given a solution in the form of a list next semester of courses that can be taken in accordance with the terms obtained from the previous semester in the form of Performance Index and the solution was given until the end of the lecture the student and provides the calculation of the total cost of each semester.